Lufenuron indirectly downregulates Vitellogenin in the boll weevil females reducing egg viability. (19th December 2020) - Cruz, Glaucilane S.; Wanderley‐Teixeira, Valéria; Antonino, José Dijair; Gonçalves, Gabriel G. A.; Costa, Hilton N.; Ferreira, Maria Clara N.; Neto, Clovis L.; Alves, Luiz C.; Santos, Fábio André B.; Teixeira, Álvaro A. C.
Abstract: Lufenuron, a molecule that belongs to the chitin synthesis inhibitors group of insect growth regulators, has a still unclear mode of action, but probably it affects chitin synthesis at a post‐transcriptional level. In this work, we report the effects of lufenuron on nutrition and reproduction in adult females of Anthonomus grandis, the main neotropical cotton pest and tried to link the effects on peritrophic matrix (PM) with egg viability. After Lufenuron treatment A. grandis females presented weight loss and less accumulation of protein and lipids probably due to PM breakdown. Also, treated females produce the same quantity of eggs as the control, although eggs from lufenuron‐treated females were less viable. After morphological and histochemical analysis, we have noticed that oocytes from lufenuron‐treated females contained less protein. Finally, lufenuron‐treated females produced at least nine times less vitellogenin (AgraVg) RNA than control females. We specifically showed that lufenuron treatment caused PM disruption and it has probably led to vitellogenin (AgraVg) downregulation in females culminating in egg unviability. The effect of lufenuron on PM leads to insect malnutrition, and this malnutrition downregulates vitellogenin among other genes. This is the first work that describes and tries to correlate the lufenuron effects on adult females. Abstract : Lufenuron causes peritrophic membrane perturbation in Anthonomus grandis female leading to weight loss and lower lipid accumulation. The lower amount of lipids affects the production of yolk protein, confirmed by microscopy and by Vitellogenin gene downregulation. Less yolk protein leads to a drastic reduction in egg viability, but not in egg production.